2005
DOI: 10.1038/sj.onc.1209080
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor YY1: structure, function, and therapeutic implications in cancer biology

Abstract: The ubiquitous transcription factor Yin Yang 1 (YY1) is known to have a fundamental role in normal biologic processes such as embryogenesis, differentiation, replication, and cellular proliferation. YY1 exerts its effects on genes involved in these processes via its ability to initiate, activate, or repress transcription depending upon the context in which it binds. Mechanisms of action include direct activation or repression, indirect activation or repression via cofactor recruitment, or activation or repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
697
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 673 publications
(723 citation statements)
references
References 97 publications
21
697
1
4
Order By: Relevance
“…Adamowicz and co-workers [47] also reported that a mutation in the Sp1 binding site of the bovine leptin gene affects its expression level. The presence of a G allele of this SNP (rSNP4) created a binding site for the zinc finger nuclear protein, YY1 (Yin Yang 1), also known as NF-E1, UCRBP or CF1, which is known to have fundamental roles in repressing and activating a diverse group of promoters; it not only initiates transcription but also activates or represses it [48,49]. YY1 is also shown to repress muscle specific expression of sarcomeric alpha-actin and c-myc genes [49].…”
Section: Discussionmentioning
confidence: 99%
“…Adamowicz and co-workers [47] also reported that a mutation in the Sp1 binding site of the bovine leptin gene affects its expression level. The presence of a G allele of this SNP (rSNP4) created a binding site for the zinc finger nuclear protein, YY1 (Yin Yang 1), also known as NF-E1, UCRBP or CF1, which is known to have fundamental roles in repressing and activating a diverse group of promoters; it not only initiates transcription but also activates or represses it [48,49]. YY1 is also shown to repress muscle specific expression of sarcomeric alpha-actin and c-myc genes [49].…”
Section: Discussionmentioning
confidence: 99%
“…This element is sufficient to regulate positively the transcription in normal cells and negatively in osteosarcoma cells. There are several possible mechanisms of the negative action of YY1 (Gordon et al, 2006). It can block the transcription through the interaction with transcription factors masking their activation domain or recruitment of corepressor molecules or, finally, by modifying histones to induce a close chromatin state (Hynes, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic mobility shift assay Nuclear extracts were prepared as described Gordon et al, 2006). Protein concentration was determined by the Bradford method .…”
Section: Chip Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the process of hepatocarcinogenesis has not yet been fully elucidated, it is considered a multifactorial and multistep process that involves the activation of oncogenes or the inactivation of tumour suppressor genes during the different stages of HCC progression. Several studies have recently shown that activation of oncogenes was involved in hepatocarcinogenesis, genes such as cyclin D1 (Deane et al, 2001), the transcription factor Yin Yang 1 (YY1) (Gordon et al, 2006), and the hedgehog pathway (Sicklick et al, 2006). Overexpression of cyclin D1 has been shown to be sufficient for the initiation of hepatocellular carcinogenesis in a transgenic mouse model (Deane et al, 2001).…”
mentioning
confidence: 99%